Structure and electrical properties evolution of B-site complex ions (Li1/4Nb3/4) modification BNT–BT ceramics. (August 2014) - Ma, X. X.; Li, W. Z.; Zeng, W. D.; Zhou, C. R.; Yang, T.; Yu, Q. Y.; Zeng, J. M.
<x content-type="archive" xml:space="preserve">Abstract</x> B-site complex ions (Li1/4Nb3/4)4+ modification (Bi1/2Na1/2)0·94Ba0·06TiO3 ceramics with compositions of (Bi1/2Na1/2)0·94Ba0·06Ti1−x(Li1/4Nb3/4)xO3 (x = 0, 0·01, 0·03 and 0·06) have been synthesised via the conventional solid state reaction. The effect of (Li1/4Nb3/4)4+ content and sintering temperature on structures and electrical properties were investigated. It was found that both compositions and sintering temperatures have no significant effect on the crystal structure, and trace (Li1/4Nb3/4)4+ addition and sintering temperatures have a great influence on the microstructure. Two obvious dielectric anomaly peaks (Td and Tm) were observed and dielectric constant for all poled specimens displayed significant frequency dispersion at Td and diffusion phase transition at Tm. The piezoelectric properties of the ceramics are insensitive to the sintering temperatures, and the composition with x = 0·03 sintering at 1150°C exhibits favourable piezoelectric properties of d33 = 155 pC N−1 and kp = 0·312.